Back from the Brink: De-escalation of Conflict During the Four Crises of the Taiwan Strait - Tshabalala, Matshepo Kholofelo (University of the Witwatersrand, Johannesburg, 2024)
The Taiwan Strait remains a critical flashpoint in East Asia, with significant implications for regional and global security. This study explores the Four Crises of the Taiwan Strait, investigating historical tensions, military strategies of brinkmanship and deterrence, and the diplomatic relations between the PRC, ROC and the USA. Through qualitative analysis, this paper endeavours to understand the causal mechanisms and strategies that have been employed to de-escalate conflict. Key aspects of this research include an examination of China's strategic objectives, the effectiveness of the use of brinkmanship to achieve these objectives, Taiwan's evolving political landscape and defence strategies, and the United States’ policy manoeuvres aimed at maintaining regional stability and protecting Taiwan. The study analyses incidents and crises to identify patterns and triggers of escalation and de-escalation. The findings highlight the importance of deterrence, diplomatic engagement, concession and appeasement. This study contributes to the broader discourse on conflict resolution and ongoing efforts to maintain peace and stability in the region.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; China; Taiwan; US; Conflict; De-escalation; Crisis; Deterrence; SDG-16: Peace, justice and strong institutions